(3TQM OjhGf TYQ GdeJdeSs - (3CHi GdMSf GdBKQe hCHi YHjOI eYeQ Hf GdeKfi Yf GdCUeYis; (3GdeJdeS , LQjQ Hf jRjO Hf YHO GdeSjM GdVLj, GdeJdeSs ((3GHh GdYjfjf YWjI s)
(3ChdgG (B:s
(3cGf SHH gLGA GdeJdeS YeQkG hGSeg YeQh Hf gfO hGSe GdeJdeS LQjQ Hf jRjO Hf YHO GdeSjM hbGd GHh YeQh gh LQjQ Hf YHO GdeSjM CNh VHjYI Hf fRGQ s
(3BNQgG (B:s
(3aNGa hbO MdJ dg ef aDGOg eMd Ldjd GdTCf bOeg GdCeQ s
(3GfXQ ai GdLRA GdChd Qbe (B357 (3hGdbSe GdKGdK GQbGe (B1592-1594 (3COHs
(3cJHgG GdfGSN Yf fSNI eMeO Hf eMehO Hf GdJdGejO GdTfbjWi GdJi cJHgG HNWg SfI (B1296(3g` hHBNQ UaMGJgG JYbjHgs
(3hGdeJdeS gh LQjQ Hf jRjO Hf YHO GdeSjM GdVLYi GdeJhai (B50 (3bg`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs